Balanced between order and disorder: a new phase in transcription elongation control and beyond. Issue 3 (27th May 2019) - Lu, Huasong; Liu, Rongdiao; Zhou, Qiang
ABSTRACT: We recently reported that the cyclin T1 histidine-rich domain creates a phase-separated environment to promote hyperphosphorylation of RNA polymerase II C-terminal domain and robust transcriptional elongation by P-TEFb. Here, we discuss this and several other recent discoveries to demonstrate that phase separation is important for controlling various aspects of transcription.